Stimulation of the bilateral anterior nuclei of the thalamus in the treatment of refractory epilepsy: two cases of subcortical band heterotopia. Issue 4 (December 2016) - Franco, Ana; Pimentel, José; Campos, Alexandre Rainha; Morgado, Carlos; Pinelo, Sara; Ferreira, António Gonçalves; Bentes, Carla
Abstract: Subcortical band heterotopia is a neuronal migration disorder that may cause refractory epilepsy. In these patients, resective surgery has yielded inadequate results. Deep brain stimulation of the anterior nuclei of the thalamus has been used for the treatment of refractory epilepsy with good results. We describe the first two patients with subcortical band heterotopia who were submitted to deep brain stimulation of the anterior nuclei of the thalamus, with evaluation of seizure outcome after 12 and 18 months of follow‐up. At these times, both showed a >50% decrease in seizure frequency and an increase in seizure freedom. Both patients had a depressive syndrome after surgery that responded fully to anti‐depressive medication in one patient and partly in the other. In both, deep brain stimulation of the anterior nuclei of the thalamus was associated with good seizure outcome. This procedure can therefore be considered in the treatment of patients with subcortical band heterotopia and refractory epilepsy. Depression may be a transient adverse event of the surgery or stimulation, however, its aetiology is probably multifactorial.